Empowering socio - economic development by addressing poverty challenges in Sabah's Developing Districts - Omar, Marja Azlima; Nohuddin, Puteri NE; Noordin, Nora Azima; AbdKadir, Zahidah; Hijazi, Hanafi A.; Hayek, Ahmed Faisal (Journal of Islamic, Social, Economics and Development, 2025)
Poverty remains one of the main barriers to socio-economic development in many of the less-developed districts of Sabah, and a better understanding of the driving forces is urgently required. This paper analyses the relationship between poverty, population dynamics, and the levels of extreme poverty using data analytics in Sabah districts. This study analyses the datasets’ demographic profiles, economic indicators, and patterns, applying correlation techniques, linear regression, and demographic analysis. The results of such analysis will provide critical information on the crucial socio-economic driving factors of poverty levels at the sub-national scale, and it pinpoints areas where interventions can be optimised for maximum impact. By analysing it, we may find the correlation between poverty levels and population density, economic activity, and access to resources. Such insights are essential in targeted interventions and efficient resource allocation, especially for economically distressed communities. The findings of this study can be used to guide policy formulation and resource allocation, leading to more effective interventions and, ultimately, sustainable and equitable prosperity in the districts of Sabah. The paper contributes to a more strategic and informed approach towards alleviating poverty in the region.